British intelligence on the North-West Frontier, 1901-1949 : India Office political and secret reports on tribes and terrorism (IDC Publishers, 2008)
"... The materials in this collection document British attempts to impose 'order' on the tribal territories.... The files describe imperial struggles with jihadist movements, and show how local leaders were able to stay out of British hands. The material covers the period 1901 to 1949, from the creation of the 'North-West Frontier Province' to 1949, by which time the Province had become an administrative region of Pakistan.... The collection, drawn from the files of the India Office Political and Secret Department archives in the British Library, consists of detailed secret and confidential reports from Frontier Agents in all the border areas, usually submitted on a weekly basis. In addition there are intelligence reviews and summaries produced by the Intelligence Bureau in Peshawar." --Publisher's Web site.